Judicial Independence: Why Does De Facto Diverge from De Jure? - Bernd Hayo; Stefan Voigt (Philipps-University Marburg, School of Business and Economics, 2021)
An independent judiciary has often been hailed as one of the most important aspects of the rule of law. Securing judicial independence (JI) via explicit constitutional rules seems straightforward and there is evidence that de jure and de facto JI are linked, at least in the long term. However, the realized degree of judicial independence often diverges significantly from the constitutionally guaranteed one. Based on theoretical conjectures and a worldwide panel dataset from 1950 to 2003, we find changes toward more parliamentary systems to be associated with a larger de jure-de facto gap, whereas the existence of procedures for amending the constitution are associated with a smaller gap. Relying on corruption levels as a proxy for the functionality of institutions, we find that higher corruption levels are associated with a wider gap between de jure and de facto JI.
Keywords: H11; K38; P51; 330; Judicial independence; constitutional compliance; de jure; de facto; de jure-de facto gap